ВЛАСНІ ІМЕНА ЯК СКЛАДОВА ЧАСТИНА МОВНОЇ КАРТИНИ СВІТУ - Мизин, Тетяна Олексіївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article deals with the fonnation process of the proper names fund. The author analyses extralinguistic factors that influenced the development of the nomination system. Etymological characteristics of proper names are defined. Proper names structure on different stages of their development is researched. The idea of meaningfulness of proper names which are considered bilateral signs is emphasized. Their semantic characteristics are singled out. It is proved that proper names are the most stable factors of the people’s culture.